The dietary carcinogen PhIP activates p53‐dependent DNA damage response in the colon of CYP1A‐humanized mice. (3rd April 2021) - Yang, Xu; Peng, Hongxia; Luo, Ziyan; Luo, Ailing; Cai, Mansi; Xu, Ling; Wang, Hong
Abstract: Species differences in the metabolism of xenobiotics by cytochrome P450 are critical in evaluating the use of experimental animals in studying toxic compounds relevant to human diseases. 2‐Amino‐1‐methyl‐6‐phenylimidazo[4, 5‐b]pyridine (PhIP), which is produced by high‐temperature cooking of fish and meat, is activated to become a carcinogen by cytochrome P4501A2 (CYP1A2) through N 2 ‐hydroxylation in humans, but is detoxified by Cyp1a2 through 4′‐hydroxylation in mice. CYP1A‐humanized (hCYP1A) mice, in which mouse Cyp1a is replaced with human CYP1A, show constitutive human xenobiotic metabolism by hCYP1A, thereby serving as a suitable model for studying PhIP. Previous studies have demonstrated that oral administration of PhIP induces colon tumors in hCYP1A mice; however, these studies used a super‐high dose, raising concerns regarding the relevance of the mechanism to human cancer. Herein, we systematically investigated PhIP‐induced colon carcinogenesis in hCYP1A mice treated with lower doses. We found that a dose 2000 times lower than that used previously, which is comparable to human daily intake levels, could induce colon tumors, albeit at a lower incidence rate. We further investigated the transcriptome changes in the colon of hCYP1A mice treated with PhIP and identified that PhIP treatment increased the expression of Bax, Btg2, Ccng1, Cdkn1a, and Trp53inp1 and decreased the expression of Igf1 and Ccnd1 . Since these genes are key components of the p53‐dependent DNA damage response, the altered expression patterns indicated PhIP‐induced DNA damage in hCYP1A mice. Together, these results prove that hCYP1A mice are suitable for studying PhIP‐induced carcinogenesis and show that PhIP is an important colorectal cancer carcinogen in human diet.